Penyuluhan Peran Santri Dalam Menjawab Tantangan Dakwah Di Era Digital - Septian Arief Budiman; Fil Isnaeni (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2019)
The digital era made a new fraction of the da'wah strategy that made the perpetrators to change the direction of da'wah in accordance with the needs of the community, the santri was a very importantcadre of Islamic da'wah and had to play an active role in developing Islamic da'wah and innovative is expected to beable to keep abreast of the development of da'wah in the digital era. Alongwiththis, lecturers of Islamic religious education have a special duty to oversee the development of Islamic indictment through the tridharma of tertiary institutions to carryout community service activities in both Islamic boarding schools the result of this activity was the creation of an understanding of the model and strategy of da'wah for santri and the readiness of santri in facing the challenges of da'wah in the digital era after interactive discussions and collaboration in the for mof a MoU between theUniversity of Pamulang and Pondok Pesantren Hidayatul Mubatdi`ienand Nurul Ummah Putri hoped that the MoU wouldestablish a stronger Islamic da'wah in the future.